Cyclic pressure on compression-moulded bioresorbable phosphate glass fibre reinforced composites - Barrera Betanzos, Fernando; Gimeno-Fabra, Miquel; Segal, Joel; Grant, David; Ahmed, Ifty (Elsevier, 2016)
The use of thermoplastic composites based on poly(lactic) acid and phosphate glass fibres over metallic alloys for clinical restorative treatment is highly beneficial due to their biocompatibility and biodegradability. However, difficulties in achieving a thorough melt impregnation at high fibre contents while limiting polymer degradation is one of the main issues encountered during their manufacture. This paper reports for the first time on the effects of pressure cycling on the mechanical properties of compression moulded polylactic acid-phosphate glass fibre composites. The strength of the composites consolidated under pressure cycling were at least 30% higher than those in which conventional static pressure was used. The marked disparity was attributed to the influence of pressure cycling on the fibre preform permeability, the melt viscosity and the capillary pressure, leading to improved fibre wet-out with respect to static pressure. Implementation of a cyclic pressure appeared to promote the occurrence of transcrystallinity in the polymer matrix as suggested by DSC traces. The fibre content influenced PLA thermal degradation since the matrix molecular weight decreased as the fibre content increased on account of the moisture adsorbed by the glass surface. However, this extent of degradation did not impair the matrix mechanical performance in the composites.